Congenital myasthenic syndromes: current diagnostic and therapeutic aspects - Finlayson, SE (2014)
This DPhil thesis presents four separate studies on diagnostic and therapeutic aspects of the congenital myasthenic syndromes (CMS). The first is a clinical characterization of syndromes associated with four novel CMS disease genes; DPAGT1, ALG2, ALG14 and GFPT1, which encode proteins involved in glycosylation pathways. These conditions are likely under-diagnosed and this characterization should help facilitate recognition of these disorders. Typically patients have prominent limb-girdle weakness and are pyridostigmine responsive. Minimal craniobulbar symptoms and the finding of tubular aggregates on muscle biopsy help to distinguish these disorders from the majority of other forms of CMS. The second is a prospective imaging study which investigates lower limb muscle MRI findings in patients with congenital myasthenia. Twenty one patients with eight CMS subtypes and ten healthy controls were imaged using T1 and short-tau-inversion-recovery (STIR) sequences. Overall a wide range of MRI appearance from normal imaging to marked abnormality was seen depending upon CMS subtype. T1 images seem to be especially abnormal in glycosylation pathway forms of CMS. No selective pattern of muscle involvement was identified. Muscle MRI could have a role in differentiating CMS subtypes, preclude the use of muscle biopsy, and may have a role in monitoring treatment effects in the future. In the final two studies separate drugs; lamotrigine and metoclopramide, are assessed as possible symptomatic treatments in transgenic mouse models of CMS. Electrophysiological measurement of neurotransmission and tests of sustained muscle effort were performed. A reduction in endplate potential decay time that could support an open-channel blocking effect of lamotrigine was observed in a model of slow channel congenital myasthenia. However, no benefit was observed during in vivo treatment trials with lamotrigine or in experiments with metoclopramide in a model of acetylcholine receptor deficiency syndrome. Overall there was no convincing evidence to clearly support therapeutic use of either agent.